Employer branding practices amongst the most attractive employers of IT and engineering sector - Gregorka, Lea (2019)
Employer branding is a marketing strategy that helps employers stay competitive in their markets. Although it is a concept used for over 20 years, its process and consequences have not yet been fully scrutinized. This study characterizes the employer branding implementation and the employers' perspective on it. By conducting ten semi-structured, in-depth interviews, the authors examine not only how employer branding practices have been applied, but also the role of human resources management in the process and used employee attraction and retention practices. The results suggest that although the employer branding process is not clearly structured, some stages can be identified as common. For that reason, the authors outline a stage divided framework and analyse each one of the identified stages. Furthermore, practical insights are provided about the company's departments roles and link them to the current state of the art. Finally, the authors suggest future investigation in particular stages of employer branding.